(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Background: With the increasing use of PET/CT and SPECT-CT imaging, monitoring occupational radiation exposure from high-energy radionuclides such as 18F-Fluorodeoxyglucose (FDG), Technetium-99m, and Iodine-131 has become essential. Objective: This study evaluates radiation exposure levels across operational areas of a nuclear medicine facility over a 24-month period and assesses compliance with Bangladesh Atomic Energy Regulatory Authority and international safety standards established by the International Atomic Energy Agency and International Commission on Radiological Protection. Methods: A longitudinal radiation survey was conducted from January 2024 to December 2025. Dose rates (μSv/h) were measured three times daily (08:00, 10:00, and 12:00) across the hot laboratory, patient environment, imaging rooms, and public areas using calibrated digital survey meters. Results: Maximum unshielded dose rates reached up to 29.8 μSv/h in PET/CT areas, while shielding reduced exposure by approximately 60–70%. Public area dose rates remained below 1.0 μSv/h. Temporal variation was minimal across 477 working days. Estimated occupational exposure remained well below the 20 mSv/year limit. Conclusion: The study confirms effective radiation protection practices, with all monitored values demonstrating compliance with international safety standards. Bangladesh J. Nuclear Med. 29(1): 64-72, 2026